If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 2y = -1 Solving -8 + 2y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2y = -1 + 8 Combine like terms: -8 + 8 = 0 0 + 2y = -1 + 8 2y = -1 + 8 Combine like terms: -1 + 8 = 7 2y = 7 Divide each side by '2'. y = 3.5 Simplifying y = 3.5
| 3(a-6)=24 | | 3x^2+3y^2+12x-18y+27=0 | | 2.5+0.25x=1.5+0.5x | | 21-3(4x-5)=9x-57 | | 4(x+3)+2=50 | | 4x+36-7x-56=83 | | 3(r-2)=24 | | 20+17w=-6+15 | | 3(2x-5)+8x-6=x/2-(5x+3) | | 7(9+15e)+19-49e+70+10e=88 | | 7(9+15e)+19-49e+70+10e=90 | | 20+17w=6+15w | | 7(9+15e)+19-49e+70+10e=91 | | -0.5+2y=-1 | | 7(9+15e)+19-49e+70+10e=98 | | 3(x+6)=81x | | -540.00+13.5g=4158.00 | | 3r-21=7 | | -540.00+13.5g=1500.00 | | 4x+121=2x+123 | | 6d-10= | | 17(t-3)(t-8)=0 | | 15.4+3.5h=1.2h-6 | | 3.3n+3.4=54+6n | | 12d-84= | | -6+15g=9+15g | | 8y-30=34 | | 3(y+2)=y+24 | | 2x+15=14-x | | (-8x+2y)(-4x+4y)= | | c=(3x+y-4)*5-5y+3 | | 5-15t=-15t-14 |